The Effect of Birth Ball Exercise on the Progress of Labor During the First Active Phase at PONED (Basic Emergence Neonatal Obstetric Services) UPTD DTP Pedes Health Center, Karawang Regency, Indonesia - Daris Yolanda Sari; Tri Rahayu Agustinawati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background.Prolonged parturition or labor that lasts longer than usual can increase the risk of complications and the potential for maternal death. The birth ball exercise, also known as the birth ball exercise or the pregnancy ball exercise, can help harness the influence of gravity to induce labor progress. This study aimed to assess the effect of birth ball exercises on the progress of labor during the first active phase at the PONED UPTD DTP Pedes Health Center, Karawang Regency, Indonesia. Methods.This study is an experimental study, where as many as 30 research subjects participated in this study. Analysis of the progress of labor was carried out using SPSS software in a univariate and bivariate manner. Results. The results of the study showed that the birth ball exercise had an effect on the progress of labor with a p-value = 0.002 (p <0.05). Conclusion, there is an influence of birth ball exercises on the progress of labor at PONED UPTD DTP Pedes Health Center, Karawang Regency, Indonesia.